Organic chemistry: a modern perspective preliminary version (United States of America. Wm. C Brown Publishers., 1996)
"The chemistry of bonded compounds has been organized along lines of reactivity rather than strictly along functional group relationship lines. For this reason, the chemistry of the nitriles is discussed with that of the aldehydes rather than with the carboxylic acids. For similar reasons, the chemistry of amines is discussed with the chemistry of alcohols, ethers and epoxides, and the chemistry of allenes is discussed with the chemistry of alkynes.The logical flow of the book, which reflects my own biases as to the best way to equalize the amount of work involved in each semester, has been organized into three loose divsions. The first of these divisions, which could be subtitled "The Fundamentals," is comprised of the first six chapters of the book, which treat the fundamental concepts of the discipline of organic chemistry. The second of the three divisions, which could be subtitled "Organic Reactivity," contains the heart of the three discussion of organic chemistry: the reactions of organic compounds. The final loose section of the book comprises Chapters 23-30, and it really concerns applications of organic chemistry in modern life or discipines other than organic chemistry itself- it could be subtitled "Organic chemistry in the wider world".
Includes indexes.
English text.
Keywords: Chemistry